Transcription, Reverse Transcription, and Amplification of Backbone‐Modified Nucleic Acids with Laboratory‐Evolved Thermophilic DNA Polymerases. Issue 7 (7th July 2021) - Song, Ping; Zhang, Rujie; He, Chuanping; Chen, Tingjian
Abstract: Backbone‐modified nucleic acids are usually more stable enzymatically than their natural counterparts, enabling their broad application as potential diagnostic or therapeutic agents. Moreover, the development of nucleic acids with unnatural backbones has expanded the pool of genetic information carriers and paved the way toward synthetic xenobiology. However, synthesizing these molecules remains very challenging due to the requirement for harsh reaction conditions and the low coupling efficiency during their traditional solid‐phase synthesis. Although enzymatic synthesis provides an attractive alternative that also allows the replication and artificial evolution of these molecules, it is crucially dependent on the availability of polymerases capable of synthesizing these backbone‐modified nucleotides. Previously, a series of thermostable polymerases that can efficiently synthesize or even amplify backbone‐modified DNA or RNA have been evolved through a polymerase evolution method based on phage display. Herein we summarize protocols to use these evolved polymerase mutants to transcribe, reverse transcribe, and PCR amplify backbone‐modified nucleic acids. We also outline the polymerase chain transcription method, developed later for the rapid production of RNA or backbone‐modified RNA with one of these evolved polymerases, SFM4‐3. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Transcription/synthesis of modified DNA/RNA from DNA templates with evolved polymerases SFM4‐3 or SFM4‐6 Basic Protocol 2 : Reverse transcription of modified DNA/RNA with evolved polymerase SFM4‐9 Basic Protocol 3 : PCR amplification of modified DNA with evolved polymerase SFM4‐3 Basic Protocol 4 : Polymerase chain transcription for the production of RNA/modified RNA oligonucleotides with evolved polymerase SFM4‐3